Automorphisms of even unimodular lattices over number fields - Kirschmer, Markus (Journal of Number Theory)
We describe the powers of irreducible polynomials occurring as characteristic polynomials of automorphisms of even unimodular lattices over number fields. This generalizes results of Gross & McMullen and Bayer-Fluckiger & Taelman.
Keywords: Algebra and Number Theory